COMPARATIVE STUDY OF EGRESS TIME ON BRAWIJAYA STADIUM AND GOR JAYABAYA KEDIRI - Moh Rezaraf Sanzani Setyawan; Cynthia Permata Dewi; Titi Rahayuningsih (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
Egress time in stadiums and sports buildings is one of the important things to consider in providing safety and tranquility for the audience in the building. The purpose of accessibility systems and adequate evacuation circulation planning in sports buildings is to provide evacuation routes that are easily accessible to spectators and minimize crowds and accumulation of people at the exit. This study aims to determine the most effective evacuation time at the Brawijaya Stadium and GOR Jayabaya in Kediri and the difference in the evacuation of spectators in a fire situation in open and closed buildings. This research uses simulation experimental research methods using Pathfinder and Pyrosim applications to find the most effective evacuation time in each building. The final results show that the addition of a radial gangway, the addition of exit doors, and the improvement of circulation flow effectively reduce the length of evacuation time in both buildings. At the Brawijaya Stadium, the evacuation time was 6 minutes and 59 seconds. GOR Jayabaya requires an evacuation time of 6 minutes and 56 seconds. In addition, there are differences in the distribution of smoke and fire in open and closed buildings. Keywords: Egress Time; Evacuation Time; Evacuation Circulation.